2001
DOI: 10.1097/00005721-200105000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Support Group for Perinatal Loss

Abstract: Grief is very individual, and not all individuals may benefit from a support group. When suggesting a support group or any intervention, timing and a caring approach are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
76
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 16 publications
0
76
0
Order By: Relevance
“…a second, only half of patients reported discussing their feelings about the loss with a physician. 15,27 DiMarco et al (2001) found physicians were rated as the least helpful of any type of staff member. 22 However, not all studies were as negative.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…a second, only half of patients reported discussing their feelings about the loss with a physician. 15,27 DiMarco et al (2001) found physicians were rated as the least helpful of any type of staff member. 22 However, not all studies were as negative.…”
Section: Resultsmentioning
confidence: 99%
“…15,27 DiMarco et al (2001) found physicians were rated as the least helpful of any type of staff member. 22 However, not all studies were as negative. One researcher found a third of parents reported a generally positive relationship with their physician and another third reported a mixed positive and negative relationship.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, when friends and family were supportive and available to the women in Van and Meleis' (2002) study, their presence was so significant that the women felt no need to seek additional aid through counseling or support groups. Women have reported finding their partners, mothers, extended families, friends and midwives as most helpful at the time of their pregnancy loss (DiMarco et al, 2001;Rajan, 1994). Additionally, many women have reported exchanges with other women who had suffered a similar loss as helpful and many of the parents within the studies further reported that they found those who were present and listened to be most helpful (DiMarco et al, 2001;Rajan, 1994).…”
mentioning
confidence: 99%
“…Women have reported finding their partners, mothers, extended families, friends and midwives as most helpful at the time of their pregnancy loss (DiMarco et al, 2001;Rajan, 1994). Additionally, many women have reported exchanges with other women who had suffered a similar loss as helpful and many of the parents within the studies further reported that they found those who were present and listened to be most helpful (DiMarco et al, 2001;Rajan, 1994). Van and Meleis (2002) reported that society provides more support for women who experience a late pregnancy loss, such as stillbirth, than for women who experience early pregnancy loss, such as miscarriage.…”
mentioning
confidence: 99%